2011
DOI: 10.1091/mbc.e11-04-0308
|View full text |Cite
|
Sign up to set email alerts
|

Retrolinkin cooperates with endophilin A1 to mediate BDNF–TrkB early endocytic trafficking and signaling from early endosomes

Abstract: Both retrolinkin and its interaction partner endophilin A1 are required for BDNF-induced dendrite outgrowth of cultured hippocampal neurons. They function sequentially in an early endocytic trafficking pathway for BDNF-activated TrkB, which provides spatiotemporal control of downstream ERK signaling from endosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…S3 B and C). Previous studies suggest that Tmem108 regulates dendritic outgrowth of hippocampal neurons (13,14). As shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…S3 B and C). Previous studies suggest that Tmem108 regulates dendritic outgrowth of hippocampal neurons (13,14). As shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Tmem108 is also present in dendrites of hippocampal neurons and has been implicated in BDNF-induced TrkB endocytosis and dendrite outgrowth in cultured neurons (13,14). However, genetic evidence is lacking regarding the in vivo function of Tmem108 and whether its mutation impairs neural development and causes schizophrenia-relevant behavioral deficits.…”
mentioning
confidence: 99%
“…However, our previous study has demonstrated that endophilin A1 interacts with retrolinkin in dendrites of mammalian central nervous system neurons and mediates the endocytic trafficking and signaling of the BDNF-TrkB ligand-receptor complex during dendrite outgrowth [22]. To further explore its function(s) in dendrites, we first examined its expression levels in mouse brain at different developmental stages.…”
Section: Endophilin A1 Localizes In Dendritic Spinesmentioning
confidence: 99%
“…Previously we have found that endophilin A1 interacts with retrolinkin and mediates BDNF-TrkB endocytic trafficking and signaling during dendrite outgrowth [22]. In this study, we used genetic manipulations in combination with biochemical and cell biological approaches to investigate the role of endophilin A1 in dendritic spines.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that an elevated level of endophilin-1 at the synapse can interfere with normal neurotransmitter signaling. Indeed, it is possible to speculate that an increase in endophilin-1 may have different effects in different locations, as endophilin-1 has been found both in the pre-synaptic neuron [75][76][77] but also the post-synaptic density [78], where it has recently been given a role in dendritic development [79]. In either case, the relative presence or absence of other signaling molecules will determine which pathways endophilin-1 can influence inside the cell.…”
Section: Consequences Of Abad and Aβ Bindingmentioning
confidence: 99%